2016
DOI: 10.1007/s40615-016-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Race and Ethnicity Documentation: a Potential Barrier in Identifying Racial and Ethnic Disparities

Abstract: BackgroundData collection on race and ethnicity is critical in the assessment of racial disparities related to health. Studies comparing clinical and administrative data show discrepancies in race documentation and attribution.MethodsSelf-reported data from two studies were compared to demographics in the electronic health record (EHR) extracted from the Biomedical Translational Research Information System (BTRIS) repository. McNemar and Bhapkar analyses were conducted to quantify the agreement of ethnicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 16 publications
2
54
0
Order By: Relevance
“…This approach highlights the importance of understanding and recording detailed self‐identified and self‐reported race and ethnicity in the context of genetic studies. Although self‐reported race and ethnicity can be influenced by an individual's social and cultural background and, thus, may not perfectly correlate with genetic ancestry, it is more reliable than assignment of race or ethnicity by another person (e.g., a healthcare professional) . However, it should be noted that self‐reported measures can be complicated by collection processes, including an incomplete selection of possible identity categories or allowing only one selection and thus failing to capture whether an individual may identify with multiple categories or none at all .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach highlights the importance of understanding and recording detailed self‐identified and self‐reported race and ethnicity in the context of genetic studies. Although self‐reported race and ethnicity can be influenced by an individual's social and cultural background and, thus, may not perfectly correlate with genetic ancestry, it is more reliable than assignment of race or ethnicity by another person (e.g., a healthcare professional) . However, it should be noted that self‐reported measures can be complicated by collection processes, including an incomplete selection of possible identity categories or allowing only one selection and thus failing to capture whether an individual may identify with multiple categories or none at all .…”
Section: Resultsmentioning
confidence: 99%
“…29 However, it should be noted that self-reported measures can be complicated by collection processes, 30 including an incomplete selection of possible identity categories or allowing only one selection and thus failing to capture whether an individual may identify with multiple categories or none at all. 29 These classification limitations can be particularly prevalent among populations with a high degree of admixture.…”
Section: Admixed Populationsmentioning
confidence: 99%
“…information is often abstracted directly from medical records. 10 Also included were several large databases compiled from electronic health record EHR data, such as the Biomedical Translational Research Information System repository, 11 and the Healthcare Cost and Utilization Project’s State Inpatient Database. 4 , 12–14 Research using datasets from large cohort studies such as the National Birth Defect Prevention Study were included if the study’s dataset was drawn directly from the participant’s medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to other findings in urban populations, our study found that non-Hispanic Black and Hispanic patients have a statistically significantly higher odds of positivity (1.5 and 2.5 respectively) [ 20 22 ]. Evidence suggests that Hispanic ethnicity is often underreported in healthcare settings, therefore even with our surname recode methodology described above, it is possible this is an underestimate of the impact on the Hispanic community [ 23 ]. Some of these disparities can be explained by the long-term disinvestment in these communities which lead to high rates of poverty, poor access to quality healthcare, and distrust of the medical community [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%